HOMO LUDENS AND "GRAY MAGIC". The violence associated with the barras bravas in the locality of Bosa in 2023 - Quintana-Arias, Ronald Fernando (2024)
With the objective of exposing the direct, cultural and structural violence associated with the hooligans of the town of Bosa in 2023 (Bogotá-Colombia). An expository case study methodology is carried out. The results exhibit a territory of invisible borders where the radicalization of violence as a social phenomenon of public order originated by the tension of interests between baristas-fans-National Police, exhibits a "Grey Magic" that generates links and causal flows in various directions. where the cycles of connection between the three categories of violence can begin at any point.It is concluded that the tension between the conception of the phenomenon of bars as a factor of free expression and personality, and on the other as facts that go against sporting honor in its various practices, are aspects of public order that affect citizen security. and they are part of the challenges faced by the National Police, making it necessary for the police to make visible the connection cycles between the three categories of violence and promote the organizational process of Homo Ludens within the Colombian Hooligans.